The social construction of enterprise strategies: Consequences of privatization - Krzysztof Konecki (Journal for East European Management Studies, 1997)
This article considers the impact of the ownership form on the formation of an organizational strategy by the main organizational actors. The following questions are discussed: Are there quick structural and strategic changes in the enterpise after a first structural transformation of ownership? What are socioorganizational consequences of privatization? Reconstructing the social construction of strategies in four Polish enterprises I will argue that privatization can be an intermediary condition influencing the construction of investment, sales or marketing strategies, but is not a necessary condition for the formulation of new strategies as such. – – Der vorliegende Artikel erörtert den Einfluß neuer Eigentumsformen auf die Formulierung von Unternehmensstrategien durch die zentralen innerorganisatorischen Akteure. Die folgenden Fragen werden diskutiert: Ist ein schneller struktureller und strategischer Wandel nach einer ersten Umwandlung der Eigentumsform in den Unternehmen zu beobachten? Welche sozio-organisatorischen Konsequenzen hat die Privatisierung? Durch eine Rekonstruktion der sozialen Konstruktion von Strategien in vier polnischen Unternehmensoll aufgezeigt werden, daß Privatisierung zwar mittelbar die Konstruktion von Investitions-, Absatz- oder Marketingstrategien beeinflussen kann, daß sie aber keine notwendige Bedingung für die Formulierung neuer Strategien an sich ist.
Keywords: 650